INDONESIAN – ENGLISH CODE-SWITCHING IN BOY WILLIAM’S YOUTUBE VIDEO ENTITLED “EPISODE 1: LIVY DAN VIOR RIBUT BESAR” - Milana Fitri Italiani; Priska Meilasari (Universitas Katolik Widya Mandala Surabaya, 2024)
The phenomenon of code-switching occurs in people's speech both through conversation and text. One of them is found in a YouTube video. This study aims to analyze the types and functions of code-switching found in the utterances of host and guest stars in Boy William's YouTube video entitled